Rifabutin Resistance Associated with Double Mutations in rpoB Gene in Mycobacterium tuberculosis Isolates - Jing, Wei; Pang, Yu; Zong, Zhaojing; Wang, Jing; Guo, Ru; Huo, Fengmin; Jiang, Guanglu; Ma, Yifeng; Huang, Hairong; Chu, Naihui (Frontiers in Microbiology, 2017)
The objective of this study was to investigate the cross-resistance between rifampin (RIF) and rifabutin (RFB) among clinical Mycobacterium tuberculosis (MTB) isolates, and the correlations between specific rpoB mutations and the minimum inhibitory concentrations (MICs) of RIF and RFB. A total of 256 RIF-resistant isolates were included from the National Tuberculosis Clinical Laboratory in China. The MICs of MTB isolates against RIF and RFB were determined by using a microplate alamarBlue assay. In addition, all the MTB isolates were sequenced for mutations in rpoB gene. 204 out of 256 isolates (79.7%) were resistant to RFB, whereas 52 (20.3%) were susceptible to RFB. RIF-resistant/INH-susceptible (RR) group had a significant lower proportion of RFB-resistance than MDR- (P=0.04) and XDR-TB group (P<0.01). DNA sequencing revealed that there were 218 isolates (85.2%) with a single mutation, 26 (10.1%) with double mutations, and 12 (4.7%) without mutation in rpoB gene. Notably, although the single substitution of Leu511Pro, Asp516Gly and His526Asn did not result in RFB resistance, 77.8% (7/9) of the MTB isolates with these double mutations became resistant to RFB. Compared with RR group (38.9%, 7/18), MDR-TB (63.5%, 106/167) had significantly higher proportion of isolates with mutations in codon 531 of rpoB gene (P=0.04). Our data demonstrate that various rpoB mutations are associated with differential resistance to RIF and RFB. A single specific mutation in codons 511, 516, 526 and 533 was linked to the susceptibility to RFB for MTB, while the strains with these double mutations irrelevantly conferring RFB resistance produced RFB-resistant phenotype.